Effect of pH-Shifted Compound Heating Treatment on the Structure and Properties of Walnut Protein Isolate - Liwen Chai; Wei Shi; Yunxia Tan; Xudong Che; Jiankang Lu; Bingyao Bai; Chunlan Zhang (Foods)
This study aims to explore the effect of pH on the solubility of walnut protein isolate (WPI) across a pH range of 7.0 to 12.0. The findings reveal that WPI solubility increased with rising pH levels, reaching a maximum solubility of 61.13% (4.79 mg/mL) at pH 12.0. Building on these results, WPI was subjected to compound heating at pH 12.0, with temperatures ranging from 60 °C to 100 °C (maintained for 30 min), to evaluate its structural and functional properties. Compared to the control group, WPI solubility peaked at 80.56% when heated to 90 °C. Additionally, its foaming capacity rose to 118.22% ± 7.34, accompanied by improved foaming stability. The average particle size decreased to 151.93 nm, while the surface charge increased to −28.33 mV. The protein subunits progressively aggregated within the range of 20.0 kDa to 14.1 kDa, and the surface hydrophobicity decreased. Scanning electron microscopy revealed that the surface morphology of the WPI became increasingly smooth with rising heating temperatures. Moreover, significant changes were observed in the secondary structure of the WPI. This study underscores the potential of pH-shifted compound heating treatment as a promising processing technique for WPI, offering key insights into the optimization of walnut protein processing.